2014
DOI: 10.1021/la5030586
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structure of Hydrophobic Surfactants at the Air/Water Interface from Molecular Level

Abstract: Understanding the behavior of fluorocarbon surfactants at the air/water interface is crucial for many applications, such as lubricants, paints, cosmetics, and fire-fighting foams. In this study, molecular dynamics (MD) simulations were employed to investigate the microscopic properties of non-ionic fluorocarbon surfactants at the air/water interface. Several properties, including the distribution of head groups, the distribution probability of the tilt angle between hydrophobic tails with respect to the xy pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Numerous MD simulation studies of lipids and surfactants at the air–water interface have been performed to investigate the monolayer properties and collapse mechanism. However, simulations of monolayers at the liquid–liquid interface are rather limited. , Shi and Guo performed all-atom MD simulation of sodium dodecyl sulfate (SDS)-type surfactants at the water-trichoroethylene interface and observed the formation of a swollen micelle for the shorter chain SDS surfactant while the longer sodium tetracosyl sulfate (STS) formed an ordered condensed phase and did not undergo a collapse transition. Li et al used dissipative particle dynamics to investigate the interfacial properties of CTAB surfactants at the oil–water interface and found that the microstructures formed depend on the oil–water ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous MD simulation studies of lipids and surfactants at the air–water interface have been performed to investigate the monolayer properties and collapse mechanism. However, simulations of monolayers at the liquid–liquid interface are rather limited. , Shi and Guo performed all-atom MD simulation of sodium dodecyl sulfate (SDS)-type surfactants at the water-trichoroethylene interface and observed the formation of a swollen micelle for the shorter chain SDS surfactant while the longer sodium tetracosyl sulfate (STS) formed an ordered condensed phase and did not undergo a collapse transition. Li et al used dissipative particle dynamics to investigate the interfacial properties of CTAB surfactants at the oil–water interface and found that the microstructures formed depend on the oil–water ratio.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1 and Figure explanations for this phenomenon [32]. The isopropylidene group interrupts the crystalline structure of the surfactant, and thus surfactant IV-D does not align or pack well at the liquid-air interface.…”
Section: Insert Schemementioning
confidence: 95%
“…where V cal is the total physical volume of surfactant molecular fragments, 54,55 and V meas is the total volume occupied by a surfactant molecule at the water-CO 2 interface. In this work, F surf for the di-CF4 molecule was calculated to be 0.788 lower than the experimental value of 0.970.…”
Section: Surfactant Coveragementioning
confidence: 99%